The Tiny Drosophila Melanogaster for the Biggest Answers in Huntington’S Disease - Piña-Muñoz, R (Multidisciplinary Digital Publishing Institute (MDPI), 2018)
The average life expectancy for humans has increased over the last years. However, the quality of the later stages of life is low and is considered a public health issue of global importance. Late adulthood and the transition into the later stage of life occasionally leads to neurodegenerative diseases that selectively affect different types of neurons and brain regions, producing motor dysfunctions, cognitive impairment, and psychiatric disorders that are progressive, irreversible, without remission periods, and incurable. Huntington’s disease (HD) is a common neurodegenerative disorder. In the 25 years since the mutation of the huntingtin (HTT) gene was identified as the molecule responsible for this neural disorder, a variety of animal models, including the fruit fly, have been used to study the disease. Here, we review recent research that used Drosophila as an experimental tool for improving knowledge about the molecular and cellular mechanisms underpinning HD. © 2018 by the authors. Licensee MDPI, Basel, Switzerland.